The Effect of Job Redesign and Workload on Job Satisfaction of Medical Employees with Burnout as a Mediation Variable at the Banjarsari Health Center, Temanggung Regency - Verawati Fajrin; Arief Subyantoro; Ambar Pujiharjanto (UPN Veteran Yogyakarta, 2022)
This observe objectives to analyze the effect of job redesign and workload on job satisfaction of clinical personnel with burnout as a mediating variable at the Banjarsari clinic, Temanggung Regency. This examine uses a quantitative approach, wherein facts and statistics are amassed via a survey the use of a questionnaire. The population on this look at were all scientific personnel of the Banjarsari Public clinic, Temanggung Regency, totaling 37 personnel. The pattern on this observe have been all scientific personnel of the Banjarsari Public health center including doctors, nurses, midwives, and scientific body of workers totaling 37 employees. The sampling method used is the census, where the entire population is sampled. The analytical technique used in this study is the Structural Equation version (SEM) with Partial Least square (PLS) 3.0. The outcomes of this have a look at suggest that job redesign has a high quality and full-size effect on job satisfaction, workload has a terrible and massive impact on job satisfaction, job redesign has a wonderful and insignificant effect on burnout, workload has a terrible and big impact on burnout, burnout has a bad and insignificant impact. on job satisfaction, burnout is not capable of mediate the effect of job redesign not directly with a poor and insignificant path on job satisfaction, and burnout isn't capable of mediate the impact of workload definitely in a roundabout way with a fine course and is not full-size on process pleasure of clinical employees on the Banjarsari clinic, District Temanggung.